2012
DOI: 10.1007/s10483-012-1561-6
|View full text |Cite
|
Sign up to set email alerts
|

Convective heat transfer from two rotating circular cylinders in tandem arrangement by using lattice Boltzmann method

Abstract: The numerical investigation of the two-dimensional laminar flow past two rotating circular cylinders in the tandem arrangement is conducted by the lattice Boltzmann method. The numerical strategy is used for dealing with curved and moving boundaries of the second-order accuracy for velocity and temperature fields. The effects of various rotational speed ratios and gap spacing are studied with the Reynolds number of 100 and the Prandtl number of 0.71. A varied range of rotational speed ratios are investigated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Sohankar et al 57 reported that a blockage ratio of less than or equal to 5% mimics an almost infinite or unconfined domain with a little effect of the artificial confining boundaries on the flow characteristics near the cylinder. There are also some numerical works reported in the literature for rotating 32 or tandem cylinders 58 carried out using a similar computational domain. In the present work, the dimensionless spacing (g*) between the cylinders is kept fixed as g* ¼ 1.5.…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Sohankar et al 57 reported that a blockage ratio of less than or equal to 5% mimics an almost infinite or unconfined domain with a little effect of the artificial confining boundaries on the flow characteristics near the cylinder. There are also some numerical works reported in the literature for rotating 32 or tandem cylinders 58 carried out using a similar computational domain. In the present work, the dimensionless spacing (g*) between the cylinders is kept fixed as g* ¼ 1.5.…”
Section: Numerical Analysismentioning
confidence: 99%
“…However, the critical rotational speed depends on the parameters including Re and g*. [30][31][32][33] The role of rotation and the cylinder spacing on the flow behavior are contradictory in nature, while the rotation tries to stabilize the flow, the cylinder spacing destabilizes it. The forced convection heat transfer over co-rotating/counter-rotating cylinders arranged in tandem or side-by-side configurations are analyzed in.…”
Section: Introductionmentioning
confidence: 99%
“…Ayyappan and Vengadesan [17] investigated the influence of placing a rotating control rod at staggering angles with respect to a stationary circular cylinder for two different values of control rod diameter and fixed rotational speed. Nemati et al [18] studied flow and heat transfer for flow past two rotating circular cylinders in tandem using Lattice Boltzmann method for selected values of spacing at Re = 100. Their work clearly suggests that further investigations need to be carried out on flow control aspect of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…When the cylinders are further separated, both cylinders co-shed vortices and their interference weakens substantially (Jo et al 2002). Nemati et al (2012) studied the flow over two rotating tandem cylinders at low Reynolds number. It shows that the flow is strongly influenced by the separating distance and the tangential speed.…”
Section: Introductionmentioning
confidence: 99%